Elastic anisotropy and thermal properties of M-B-N (M = Al, Ga) systems using first-principles calculations. (January 2023) - Yang, Chen; Duan, Yonghua; Yu, Jie; Peng, Mingjun; Zheng, Shanju; Li, Mengnie
Abstract: In this paper, the elastic properties, Debye temperatures, thermal conductivities, and sound velocities of M-B-N nitrides are explained systematically by considering the first-principles calculations based on density functional theory. The three-dimensional (3D) surface construction and planar projection of elastic anisotropy indicated that the elastic modulus is in the sequence of M3 BN4 > MBN2 > MB3 N4 and Al–B–N nitrides > Ga-B-N nitrides. The thermal properties were analyzed according to elastic modulus, and the obtained Debye temperatures, sound velocities and minimum thermal conductivities of these M-B-N nitride are anisotropic. AlB3 N4 has the highest Debye temperature, indicating that AlB3 N4 has the highest hardness and the largest minimum thermal conductivity among these nitrides. Highlights: The M-B-N nitride are mechanically stable due to that their elastic constants meet respective mechanical stability criteria. The elastic modulus is anisotropic with the order ofAl3 BN4 > Ga3 BN4 > AlBN2 > GaBN2 > AlB3 N4 > GaB3 N4 . Poisson's ratio v, G H / B H and Cauchy pressures indicate that all these M-B-N nitrides are brittle. The minimum thermal conductivity is anisotropic in the order of AlB3 N4 > GaB3 N4 > AlBN2 > Al3 BN4 > GaBN2 > Ga3 BN4 .